A documentary study of the excavations of Al-‘Abed Castle in Rosetta - Mahmoud Ahmed Darwish (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2020)
In 1987, I made the scientific documentary of thirteen castles (fort) on the Mediterranean coast between the two ports of Rosetta and Abu Qir, all dating back to the era of Muhammad Ali,The castles were in a deplorable state, given that the British army destroyed them when they invaded Egypt in (1881).Most of these castles are surrounded by sand dunes, and then, I immediately began preparing for excavations in one of these castles, which resulted in the discovery of the castle and the identification of its architectural elements. In 1989, we began excavating the first of these castles, the Al-’Abed Castle, through which it was possible to uncover all parts of the castle, including the southern façade, the two towers on both ends, the entrance, rooms and shooting holes with cannons, and then, a number of sketches were made that will be shown during the study. The Al-‘Abd Castle and other castles in Rosetta, starting from Qaitbay Castle and the castles on the Mediterranean coast from the mouth of the Rosetta branch to Abu Qir, are among the most important indications of the historical and architectural importance of the military fortifications in Rosetta. The stages of excavations in this castle and its architectural elements. The excavation work carried out by the researcher was the beginning of the road to uncover the secrets of this castle as a model for the castles of Muhammad Ali, and it helped highlight the fortifications and define their features, solve all their mysterious symbols, and define all their architectural and defense elements. The study dealt with the description of the castle, and the excavations helped to show all the elements that were focused on by developing a descriptive study of it as one of the models of castles dating back to the era of Muhammad Ali, and it is known that there was a fundamental similarity between the castles of Muhammad Ali in terms of the basic elements with some differences in the internal details. The researcher was the head of the excavation expedition that discovered this castle, and these excavations have had a wide resonance, as it is the first time that a fortress dating back to the era of Muhammad Ali has been uncovered.